Money, Deficit and Public Debt in the United States - Tabellini, Guido; Via, Vincenzo La (The Review of Economics and Statistics, 1989)
This study estimates the underlying parameters in a dynamic game between the fiscal and monetary authorities over the determination of public debt. These estimates reveal the policymakers attitude towards the goal of stabilizing the time path of public debt. The central finding is that, in the United States during the 1955-85 period, this goal has been pursued by the fiscal authority, but not by the central bank. Monetary policy has not monetized the stock of public debt outstanding, whereas cyclically-adjusted, net of interest, fiscal deficits have been reduced to offset increases in the stock of debt in circulation. Copyright 1989 by MIT Press.